DIFFERENTIATED INSTRUCTION AT HIGHER EDUCATION INSTITUTIONS: BIBLIOMETRIC ANALYSIS - Terletska, Tetiana (The Modern Higher Education Review, 2024)
The article examines the implementation of differentiated instruction in higher education institutions through bibliometric analysis using Scopus database data and Bibliometrix software. Differentiated instruction addresses diverse student needs, interests, and capabilities, aligning with global educational trends emphasizing flexibility, inclusivity, and lifelong learning. Historically focused on special and gifted education, recent studies highlight its broader applications, including STEM, language learning, and online education. The analysis includes 129 relevant publications, representing 13% of all differentiated instruction related research in Scopus. The main areas in the research topic are foreign language teaching, inclusive education, innovative pedagogies, and teacher training. Prominent trends include the integration of differentiated instruction in technology-enhanced learning, its impact on student engagement and academic performance, and its role in fostering inclusivity and equity. The study underscores the necessity of teacher readiness and training to implement differentiated instruction effectively. By mapping current knowledge and identifying gaps, the article provides a foundation for advancing differentiated instruction practices in higher education institutions, emphasizing its potential to enhance student outcomes and educational equity in a digitalised context.